2004
DOI: 10.1111/j.1365-4632.2004.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Zosteriform skin metastases

Abstract: A 66‐year‐old woman was referred for evaluation of a rash on the leg. She had a 1‐year history of stage IV bronchogenic adenocarcinoma with previous metastases to the right first metatarsal‐phalangeal (MTP) joint and a left supraclavicular lymph node. She underwent six cycles of chemotherapy with paclitaxel (Taxol; Bristol‐Myers Squibb Company, Princeton, NJ, USA) and carboplatin (Paraplatin; Bristol‐Myers Squibb Company, Princeton, NJ, USA) as well as palliative radiation therapy to the metastasis sites. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…They reported that the lesions were localized at the anterior thoracic wall in 75 patients. Spontaneous pain was observed in many patients with zosteriform cutaneous metastases just like in our case and most of the cases were given antiviral treatment (2,10).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They reported that the lesions were localized at the anterior thoracic wall in 75 patients. Spontaneous pain was observed in many patients with zosteriform cutaneous metastases just like in our case and most of the cases were given antiviral treatment (2,10).…”
Section: Discussionmentioning
confidence: 93%
“…There are many theories about the occurrence of zosteriform cutaneous metastasis which include occurrence due to koebnerization at the region which previously had herpes zoster infection, perineural spread, lymphatic spread, spread in dorsal root ganglion veins through fenestral route, or coincidentally during surgery (2,10,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which cancer cells spread in zosteriform skin metastasis remains unknown but proposed theories include lymphatic or haematogenous spread, neural spread, surgical implantation of tumor cells, and koebnerization [1].…”
Section: Case Reportmentioning
confidence: 99%
“…Although rare, there were 19 published cases of cutaneous metastatic adenocarcinoma arising as a zosteriform eruption [1][2][3][4][5].…”
Section: Case Reportmentioning
confidence: 99%